Lessons Learned From a Qualitative COVID-19 Investigation Among Essential Workers With Limited English Proficiency in Southwest Kansas. (April 2022) - Jaramillo, Jahn; Moran Bradley, Belen; Jentes, Emily S.; Rahman, Mehabuba; Sood, Neha Jaggi; Weiner, PhD, Judith; Marano, Nina; Ahmed, Farah S.; Kumar, Gayathri S.
In this commentary, we briefly describe our methodology in conducting a remote qualitative investigation with essential workers from southwest Kansas, and then describe some key considerations, challenges, and lessons learned in recruiting and conducting interviews remotely. From August 4, 2020 through August 26, 2020, Centers for Disease Control and Prevention (CDC) staff conducted five phone interviews with culturally and linguistically diverse employees in southwest Kansas to understand COVID-19 knowledge, attitudes, and practices and communication preferences. Our experience details the potential challenges of the federal government in recruiting individuals from these communities and highlights the possibilities for more effectively engaging health department and community partners to support investigation efforts. Optimizing recruitment strategies with additional participation from community partners, developing culturally and linguistically appropriate data collection tools, and providing supportive resources and services may augment participation from refugee, immigrant, and migrant (RIM) communities in similar remote investigations.